Physical stability and release properties of lumefantrine amorphous solid dispersion granules prepared by a simple solvent evaporation approach - Niraj S. Trasi; Sonal V. Bhujbal; Dmitry Y. Zemlyanov; Qi (Tony); Lynne S. Taylor (Elsevier, 2020)
Amorphous solid dispersions (ASDs) of lumefantrine, which has low aqueous solubility, have been shown to improve bioavailability relative to crystalline formulations. Herein, the crystallization tendency and release properties of a variety of lumefantrine ASD granules, formed on a blend of microcrystalline cellulose and anhydrous lactose, prepared using a simple solvent evaporation method, were evaluated. Several polymers, a majority of which contained acidic moieties, and different drug loadings were assessed. Crystallinity as a function of time following exposure to stress storage conditions of 40 °C and 75% relative humidity was monitored for the various dispersions. Release testing was performed and ASD characteristics were further evaluated using infrared and X-ray photoelectron spectroscopy (XPS). A large difference in stability to crystallization was observed between the various ASDs, most notably depending on polymer chemistry. This could be largely rationalized based on the extent of drug-polymer interactions, specifically the degree of lumefantrine-polymer salt formation, which could be readily assessed with XPS spectroscopy. Lumefantrine release from the ASDs also varied considerably, whereby the best polymer for promoting physical stability did not lead to the highest extent of drug release. Several formulations led to concentrations above the amorphous solubility of lumefantrine, with the formation of nano-sized drug-rich aggregates. A balance between the ability of a given polymer to promote physical stability and drug release may need to be sought.